Late Ottoman Discourses on Nationalism and Islam and the Contributions of Russia’s Muslims - Mustafa Gökçek (International Institute of Islamic Thought, 2015)
This study focuses on the early twentieth-century nationalist and Islamist discourses in the Ottoman Empire. Particularly after the 1908 coup, Turkish and Arab nationalism spread among the intellectuals. Under the Committee of Union and Progress (CUP) party’s leadership, Turkish nationalists received tremendous support to spread their views through associations and publications. Some of them defended the compatibility of Turkish nationalism with Islam. In response, traditional Islamist intellectuals argued that Islam was opposed to nationalism and tribalism and pointed out the potential dangers of pursuing nationalism in a multiethnic society. This article mostly focuses on the nationalist and traditionalist intellectuals. Among the first group was Halim Sabit, a Kazan Tatar who moved to Istanbul from Russia to pursue religious studies at a madrasa. He eventually became heavily involved in nationalist circles and published articles in Sırat-i Mustakım and İslam Mecmuası on how Islam allowed nationalism and how Turkish nationalism could serve Islam. At the same time, he participated in a trip to the Middle East to convince the Arabs of the need for Islamic unity. In contrast to Musa Kazım, Said Nursi, and other intellectuals, Sabit emphasized the unity of Muslim nations within the empire.